Residents' acceptability and response to the water-pricing policy to reduce marine pollution caused by domestic sewage - Xu, Zhihua; Wang, Chuwei; Li, Shuqin; Shan, Jingzhu (Frontiers in Marine Science, 2023)
Domestic sewage has huge negative impacts on marine environment. This paper discusses whether residents can accept the water pricing policy that collect funds to improve sewage treatment technologies to reduce marine pollutants by raising water price. Firstly, the contingent valuation method is used to elicit residents’ acceptability of water price increase. The results show that residents can accept an increase of 0.90 CNY/m3 in water price on average in Qingdao, China. Additionally, we find that people with low income shows low acceptability of the water pricing policy. Secondly, the contingent behavior method is applied to observe residents’ responses to the pricing policy. The results show that water price plays a positive role in promoting residents’ willingness to reduce water use. The information transmission will encourage people to adopt water-saving behavior and strengthen the impact of water pricing policy on water-saving behavior. This paper provides important implications to establish water-pricing policy to reduce the negative impacts of domestic sewage on the marine environment.